EANO–EURACAN clinical practice guideline for diagnosis, treatment, and follow-up of post-pubertal and adult patients with medulloblastoma. Issue 12 (December 2019) - Franceschi, Enrico; Hofer, Silvia; Brandes, Alba A; Frappaz, Didier; Kortmann, Rolf-Dieter; Bromberg, Jacoline; Dangouloff-Ros, Volodia; Boddaert, Nathalie; Hattingen, Elke; Wiestler, Benedikt; Clifford, Steven C; Figarella-Branger, Dominique; et al.
Summary: The European Association of Neuro-Oncology (EANO) and EUropean RAre CANcer (EURACAN) guideline provides recommendations for the diagnosis, treatment, and follow-up of post-pubertal and adult patients with medulloblastoma. The guideline is based on the 2016 WHO classification of tumours of the CNS and on scientific developments published since 1980. It aims to provide direction for diagnostic and management decisions, and for limiting unnecessary treatments and cost. In view of the scarcity of data in adults with medulloblastoma, we base our recommendations on adult data when possible, but also include recommendations derived from paediatric data if justified. Our recommendations are a resource for professionals involved in the management of post-pubertal and adult patients with medulloblastoma, for patients and caregivers, and for health-care providers in Europe. The implementation of this guideline requires multidisciplinary structures of care, and defined processes of diagnosis and treatment.